2019
DOI: 10.3390/ma12213535
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Shock Absorption Capacities of Custom Fabricated Mouthguards Using a Triangulation Sensor

Abstract: This in-vitro study compares the shock absorption qualities of five mouthguard designs measured with a triangulation laser sensor during small hard object collisions. The aim was to investigate the impact of different labial designs on mouthguard performance. Methods: Five different custom-fabricated ethylene vinyl acetate (EVA) types of mouthguards with varying thickness and different labial inserts (polyethylene terephthalate glycol-modified (PETG), nylon mesh, air space) were tested with a triangulation las… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…It was concluded that thickness increase by insertion of additional layers results in protective properties of the construction. Sarac et al [24] obtained similar results.…”
Section: Limitation Statementmentioning
confidence: 58%
See 1 more Smart Citation
“…It was concluded that thickness increase by insertion of additional layers results in protective properties of the construction. Sarac et al [24] obtained similar results.…”
Section: Limitation Statementmentioning
confidence: 58%
“…Mouthguard thickness has a significant impact on the patient’s comfort. Recent studies considered an influence of the mouthguard’s thickness on its performance [ 22 , 23 , 24 ]. Westerman et al [ 22 ] revealed that the rational thickness for an EVA mouthguard is 4 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Additive manufacturing of a biocompatible silicone in 20A, 40A and 60A Shore hardness has been reported recently [ 19 ]. However, higher Shore A values starting from 85A are required for a sufficient shock absorbance [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…An average thickness of 4 mm is considered to be optimal for a MG to withstand the expected traumatic impact while not interfering with the wearer’s comfort [ 7 , 8 , 9 , 10 ]. The thickness of 4 mm was tested in material combinations and proved to have a better shock absorbance than multilayer designed MGs [ 3 , 11 , 12 ]. Today, such multilayer custom MGs are manufactured using an analog method.…”
Section: Introductionmentioning
confidence: 99%
“…The PETG is a thermoplastic commonly used in odontology in the technique of vacuum thermoforming for the production of protective devices [21,22] and orthodontic devices [23,24], being biocompatible, resistant, easy to finish, low cost and with a simpler technique application when compared to PMMA. Despite clinical reports of the use of PET as intraoral radiotherapy positioners, no study was found regarding the use of PETG through a dosimetry evaluation.…”
Section: Introductionmentioning
confidence: 99%